Brucellosis sacroiliitis in a 10-year-old boy: A rare clinical entity - Syed Faisal Afaque; Udit Agrawal; Vikas Verma (Journal of Orthopaedic Reports)
Brucellosis is a zoonotic infection caused by Brucella species, commonly presenting with fever, fatigue, and musculoskeletal symptoms. Sacroiliitis, a rare complication of brucellosis, often presents as low back pain and is frequently misdiagnosed, leading to chronic complications. This case report is of a 10-year-old boy diagnosed with brucellosis sacroiliitis, a condition seldom reported in the paediatric population. The patient presented with progressive low back pain, radiating to the right hip, along with intermittent fever and weight loss. His history included consumption of unpasteurized milk which is a known risk factor for brucellosis. Initial physical examination revealed tenderness over the right sacroiliac joint, and MRI findings were suggested of sacroiliitis. Serological tests for Brucella antibodies were positive, confirming the diagnosis. The patient was treated with a six-month regimen of rifampicin and doxycycline, along with analgesics. Significant clinical improvement was observed within one week, with complete resolution of symptoms and normal inflammatory markers by six weeks. At the six-month follow-up, the patient remained asymptomatic. This case highlights the importance of considering brucellosis in differential diagnoses for unexplained musculoskeletal symptoms in endemic regions, particularly in children. Early recognition and appropriate antibiotic therapy are crucial for optimal outcomes and prevention of long-term complications.